The evaluation of the link between talent and potential of human resources - Daneci-Patrau, Daniel (Studies and Scientific Researches. Economics Edition, 2010)
The term “talent”, assigned to distinctive employees was certainly the past years leitmotif. Nowadays, the organizations need performance and for this reason they turn their attention towards the instruments which help them discover and explore the potential in people. In a context in which the crisis affects directly the labor market and the employees are more and more afraid of the possibility of losing their jobs, the incertitude and the insecurity appear more often. Especially, in these times, the need for continuous feedback, particularly connected to the decisions taken by the management, to the results of the company, to the adopted strategy and the way in which it reflects itself in the employees’ activity, is felt by all employees, no matter their role or their position. In this article, I presented the personal profile of the successful manager and the execution stages with the related conclusions in an evaluation program for the potential of the human resources in a sales company.